Out of this world ebook - Dean, James (Pete the Cat., 2017)
Blast off into space with New York Times bestselling author and artists James Dean and everyone's favorite cat-stronaut, Pete the Cat, in Pete the Cat: Out of This World. When Pete heads off to space camp, he gets to float in zero gravity, build rockets, and even goes on an extraordinary interstellar mission that is out of this world—literally. Houston, ready to rock out with Pete the Cat! Don't miss Pete's other storybook adventures, including Pete the Cat: Construction Destruction, Pete the Cat: Cave-cat Pete, Pete the Cat and the Treasure Map, Pete the Cat: Robo-Pete, and more!